Bioactive glass-ceramic bone repair associated or not with autogenous bone: a study of organic bone matrix organization in a rabbit critical-sized calvarial model - Biguetti, Claudia Cristina (2018)
Objective: The aim of the study was to analyze bone matrix (BMX) organization after bone grafting and repair using a new bioactive glass-ceramic (Biosilicate®) associated or not with particulate autogenous bone graft. Material and methods: Thirty rabbits underwent surgical bilateral parietal defects and divided into groups according to the materials used: (C) control—blood clot, (BG) particulate autogenous bone, (BS) bioactive glass-ceramic, and BG + BS. After 7, 14, and 30 days post-surgery, a fragment of each specimen was fixed in − 80 °C liquid nitrogen for zymographic evaluation, while the remaining was fixed in 10% formalin for histological birefringence analysis. Results: The results of this study demonstrated that matrix organization in experimental groups was significantly improved compared to C considering collagenous organization. Zymographic analysis revealed pro-MMP-2, pro-MMP-9, and active (a)-MMP-2 in all groups, showing gradual decrease of total gelatinolytic activity during the periods. At day 7, BG presented more prominent gelatinolytic activity for pro-MMP-2 and 9 and a-MMP-2, when compared to the other groups. In addition, at day 7, a 53% activation ratio (active form/[active form + latent form]) was evident in C group, 33% in BS group, and 31% in BG group. Conclusion: In general, BS allowed the production of a BMX similar to BG, with organized collagen deposition and MMP-2 and MMP-9 disponibility, permitting satisfactory bone remodeling at the late period. Clinical relevance: The evaluation of new bone substitute, with favorable biological properties, opens the possibility for its use as a viable and efficient alternative to autologous bone graft.